The IASLC Lung Cancer Staging Project: Background Data and Proposed Criteria to Distinguish Separate Primary Lung Cancers from Metastatic Foci in Patients with Two Lung Tumors in the Forthcoming Eighth Edition of the TNM Classification for Lung Cancer. Issue 5 (May 2016) - Detterbeck, Frank C.; Franklin, Wilbur A.; Nicholson, Andrew G.; Girard, Nicolas; Arenberg, Douglas A.; Travis, William D.; Mazzone, Peter J.; Marom, Edith M.; Donington, Jessica S.; Tanoue, Lynn T.; Rusch, Valerie W.; Asamura, Hisao; et al.
ABSTRACT : Introduction: : It can be difficult to distinguish between a second primary and a metastasis in patients with lung cancer who have more than one pulmonary site of cancer. Methods: : A systematic review of the literature was conducted by a subcommittee of the International Association for the Study of Lung Cancer Staging and Prognostic Factors Committee to develop recommendations to identify second primary lung cancers. The process entailed review of knowledge relating to the mechanism of metastasis, determination of clonality, and outcomes of patients with resected tumors. Results: : It is easier to determine that two tumors are different than that they are the same; finding similarities does not establish that they are the same. For example, most second primary lung cancers are of the same histotype. Few criteria are reliable by themselves; these include different histologic cancer types or matching DNA breakpoints by sequencing and a comprehensive histologic assessment of resected specimens. Characteristics that are suggestive but associated with potential misclassification include the presence or absence of biomarkers, imaging characteristics, and the presence or absence of nodal involvement. Conclusions: : Clinical and pathologic (i.e., after resection) criteria are presented to identify two foci as separate primary lung cancers versus a metastasis. Few features are definitive; many commonly used characteristics are suggestive but associated with a substantial rate of misclassification. Careful review by a multidisciplinary tumor board, considering all available information, is recommended.